Parvalbumin interneuron deficiency in the prefrontal and motor cortices of spontaneously hypertensive rats: an attention-deficit hyperactivity disorder animal model insight - Bogdańska-Chomczyk, Ewelina; Równiak, Maciej; Huang, Andrew Chih-Wei; Kozłowska, Anna (Frontiers in Psychiatry, 2024)
Attention-deficit/hyperactivity disorder (ADHD) is characterized by developmental behavioral inhibition impairments, resulting in impulsivity and hyperactivity. Recent research underscores cortical inhibition deficiencies in ADHD via the GABAergic system, crucial for maintaining excitatory-inhibitory balance in the brain.This study explored postnatal changes in parvalbumin (PV) immunoreactivity, indicating GABAergic interneuron types, in the prefrontal (PFC) and motor (MC) cortices of spontaneously hypertensive rats (SHRs) -an ADHD animal model. Examining PV+ cells, associated with dopamine D2 (D2) receptors and dopamine's impact on GABA synthesis, we also investigated changes in D2 and tyrosine-hydroxylase (TH) immunoreactivity.Brain sections from 4-10-week-old SHRs and Wistar-Kyoto rats (WKYs) were immunohistochemically analyzed, comparing PV+, D2+ cells, and TH+ fibres densities across age-matched SHRs and WKYs in specific PFC/MC regions. Results revealed significantly reduced PV+ cell density in SHRs -prelimbic (~20% less), anterior cingulate (~15% less), primary (~15% less), and secondary motor (~17% less) cortices. PV+ deficits coincided with D2 upregulation in pre-pubertal SHRs and TH downregulation, predominantly in pubertal/post-pubertal SHRs.In conclusion, reduced PV+ cells in various PFC regions may contribute to inattention/behavioral alterations in ADHD, while MC deficits may manifest as motor hyperactivity. D2 upregulation and TH deficits may impact GABA synthesis, exacerbating behavioral deficits in ADHD. These findings not only shed new light on ADHD pathophysiology but also pave the way for future research endeavors.